Observation of Diffuse Galactic Light Near the Galactic Center with ONC-T on Board Hayabusa2 - Kei Sano; Yuto Tome; Kana Kurosaki; Kohji Tsumura; Shuji Matsuura; Kohji Takimoto; Takahiro Iwata; Manabu Yamada; Tomokatsu Morota; Toru Kouyama; Masahiko Hayakawa; Yasuhiro Yokota; et al. (The Astrophysical Journal, 2025)
Diffuse Galactic light (DGL) is starlight scattered by interstellar dust. In visible wavelengths, earlier studies observed DGL toward regions of low optical depth in high Galactic latitude, and show marginal consistency with a theoretical model assuming single scattering by dust grains. However, a model for DGL in regions of high optical depth has not been established. In this study, we analyze wide-field imaging data toward a region of high optical depth near the Galactic center, which was obtained with the Optical Navigation Camera on board the Hayabusa2 spacecraft. The data are reduced by dark-current and stray-light subtraction, flat-field correction, and sensitivity calibration for the DGL measurement. In the image, we select dark low-intensity areas where background starlight is highly absorbed by interstellar dust, and extract the DGL component by masking pixels contaminated by stars. As a result, we find that the DGL intensity decreases toward high optical depth, and this trend is reversed from the previous measurements in optically thin regions. To explain the observed trend, we introduce DGL models inferred from a radiative transfer equation in a plane-parallel dusty slab. By assuming literature values for the albedo and scattering asymmetry factor of interstellar dust, the measured DGL intensity can be fitted by a model in which a dust slab without internal emitters is illuminated by backside stars.